Avaliação do efeito do cigarro na expressão gênica e proteica em carcinoma epidermoide de cavidade oral: relação do tabagismo com elementos responsivos de hipóxia e estresse oxidativo - Oliveira, Mayara Mota de (2021)
Squamous cell carcinoma of the oral cavity (OSCC) is associated with high mortality rates and its main risk factor is smoking. In relation to tobacco, it is composed by more than 7000 substances including nicotine. Nicotine contribution to carcinogenesis is related to the activation of multiple signaling pathways that also regulate the progression, growth, and metastasis of tumors by stimulating nicotinic acetylcholine receptors (nAChRs). Nicotine exposure can simulate the effects of hypoxia, and promote up-regulation in the expression of pathway-related genes such as HIF-1α, VEGF-A, FIH, PHD3. In addition, the constituents of tobacco are responsible for the generation of reactive oxygen species (ROS), which disturb cell homeostasis and promote damage to DNA, RNA, lipids, and proteins. Among the antioxidant defense mechanisms for maintenance of homeostasis and DNA repair, a set of proteins that act to reduce oxidative stress are mobilized. Protein superoxide dismutase (SOD) is the main intracellular defense mechanism against oxidative reactions, and Apurine/apyrimidinic endonuclease/redox factor (APE-1/REF-1) acts at the base excision repair pathway. This study aimed to understand the role of nicotine and smoking, through cigarette extract (CSE), in the expression of genes and proteins in the hypoxia, oxidative stress, and repair pathways in cell lines of squamous cell carcinoma of the cavity oral (SCC-9) and oral keratinocytes with dysplasia (DOK), and their associations with the prognosis and survival of 137 patients with OSCC, smokers and non- smokers. Cigarette Smoke Extract (CSE) has been shown to have a greater impact on reducing cell migration in the DOK lineage, and mobilizes SOD-1 expression in concentration-dependent response, while APE-1/REF-1 show a different kind of regulation being the response time-dependent in SCC-9 cells. In vivo, smoking contributed to the strong expression of SOD-1, and its positive expression was significantly associated with tumor size, differentiation, in addition to being a protective factor for better disease-free survival. APE-1/REF-1 expression was associated with tumor size and disease-specific survival. Regarding nicotine exposure, SCC-9 demonstrates to be more responsive to cellular modulation and response to hypoxia and oxidative stress, with exhibiting on the increased expression of SOD-1, APE-1/REF-1, and HIF-1α. Together, our findings demonstrate that the degree of malignancy may be a variable related to the time of activation of cellular mechanisms of overall survival in response to ROS and hypoxia in smokers.